Institutional Support for Talent Development: Employees’ Insight in Community Colleges, Nepal - Mainali, Hari Lal (Apex Journal of Business and Management, 2025)
This study investigates institutional support for talent development in community colleges of Madhesh Pradesh, Nepal, focusing on employees’ insights and gender-based differences. Grounded in Human Capital Theory, the research explores how institutional practices affect employee insight of talent development. A descriptive and exploratory design was employed, drawing data from 205 teaching faculties using a structured questionnaire. Quantitative analyses, including regression and ANOVA, revealed a statistically significant model explaining variance in employee insights. Peer learning emerged as the strongest positive predictor, while recognition and reward systems showed a significant but negative relationship, indicating potential gaps between institutional efforts and employee expectations. Gender-based analysis revealed males aligned more with growth opportunities and recognition practices, whereas females favored peer learning and feedback mechanisms, with peer learning showing the most significant gender disparity. Other institutional practices such as workshop participation and inclusive work environments were found statistically insignificant, suggesting inadequacies in implementation. The study highlights the need for more inclusive, transparent, and evidence-based talent development strategies. It also identifies gaps in current practices and emphasizes the importance of peer learning and gender-responsive frameworks. Limitations include the study’s cross-sectional design, reliance on self-reported data, and exclusion of non-binary perspectives, underscoring the need for broader, more inclusive future research.